(untitled) - English Language Services (New York, 1995)
The book consists of ten units. Each unit contains a group of fifteen base sentences related to a meaningful situation. Units in this book contain Base Sentences, Intonation practice, Substitution Drills, Conversation, and Exercises. Beginning with this book, a Reading Practice section is added to each unit
Keywords: english language - study and teaching